Education and culture in human behavior from the theory of Advanced Education / Educación y cultura en el comportamiento humano desde la teoría de la Educación Avanzada - Alpízar Caballero, Lourdes Bárbara; Betancourt Torres, Isis; Cardoso Camejo, Lidisbet (Archivos del Hospital Universitario "General Calixto García", 2023)
Introduction: Culture includes the processes of intellectual, spiritual and aesthetic development of human events, it includes the intellectual, economic and social progress of a country. Education plays a fundamental role in these processes, however, the relationship between culture and human behavior has not been verified in the information sources consulted on the intellectual production of Advanced Education published until 2022 in Scielo, Scopus, Redalyc and DOAJ, their relations with culture and culture with human behavior have not been declared. Objective: To establish the interrelation between culture, education and human behavior from the Theory of Advanced Education. Development: In order to substantiate the relationship under study and offer the results, a qualitative investigation was carried out in which the inductive-deductive method, documentary analysis, systematization and triangulation of the results were applied. For its better understanding, it was structured in three parts: The concept of culture and its interrelation with education, Education and the theory of Advanced Education, and the Interrelations between human behavior, culture and Advanced Education. Conclusions: The interrelationship between culture, education and human behavior from the Advanced Education Theory is evidenced in the dimensions declared for the improvement of human behavior by this theory from Marti's pedagogical, humanist and axiological thought based on Cuban social ideas of national order, identity and patriotic values. All of them root culture from the specific social historical context.